158k views
5 votes
How to solve x2+6x+5=0 using the quadratic formula

2 Answers

6 votes
So, we know, that the quadratic formula is:
x=
\frac{-b (+)/(-) \sqrt{b^(2) -4ac} }{2a}
If we plug in a,b and c, we get:
x=
\frac{-6 (+)/(-) \sqrt{6^(2)-(4)(1)(5) } }{(2)(1)}
Which would then be:
x=
(-6 (+)/(-) √(16) )/(2)

x=
(-6 (+)/(-)4 )/(2)

x=-3
(+)/(-)2

x=-1 and -5

So, the answers would be -1 and -5.
User Borduhh
by
6.3k points
2 votes
Its really easy if you think about it.. I got (x+5)(x+1)
User Isaac Truett
by
6.3k points